The Effects of Planar Microstrip Patch Antennas on Cross Polarised X-Ray Radiations - Agnihotri, Aditiya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
An MPA, or microstrip patch antenna, is an antenna made out of a metal patch mounted on a grounded base. The shape of the metallic patch is flexible and may be a rectangle, a circle, a triangle, etc. For decades, microstrip patch antennas have played a crucial role in wireless communication systems. The Mobile Phone Industry has come to rely heavily on the MPA in recent years. The primary goals of this study are to minimise XP radiation, suppress a higher-order mode that isn't desired (a spurious mode), shrink the size of planar RMPA, and increase its gain for use at lower frequencies (S-band, 2–4 GHz). A pair of symmetrical metallic stubs loaded between the ground and the patch, a pair of symmetrical linear slots etched in the ground plane as DGS(Defected Microstrip Surface) (DMS), and the incorporation of a rectangular slot etched in the radiating patch as DMS(Defected Ground Structure) near the non-radiating edge all contribute to this goal. The HFSS simulator was used to conduct analyses of the investigated parameters, including return loss, gain, radiation pattern, etc.